The Empire State Collection : Art For The Public - Sandler, Irving; Empire State Plaza Art Commission, Albany (NY) (New York : Harry N. Abrams Inc. Publishers, 1987)
Richard Anuszkiewicz ; Ronald Bladen ; Roger Bolomey ; Ilya Bolotowsky ; Lee Bontecou ; James Brooks ; Lawrence Calcagno ; Alexander Calder ; Gene Davis ; Herbert Ferber ; Naum Gabo ; Fritz Glarner ; Adolph Gottlieb ; Philip Guston ; Dimitri Hadzi ; Grace Hartigan ; Will Horwitt ; Paul Jenkins ;l Alfred Jensen ; Ellsworth Kelly ; Lyman Kipp ; Franz Kline ; Alexander Liberman ; Seymour Lipton ; Alvin D. Loving ; Sven Lukin ; Conrad Marca-Relli ; Clement Meadmore ; Forrest Myers ; Louise Nevelson ; etc.
Engels
boek